PENYUSUNAN SKENARIO KEBIJAKAN UNTUK PENGEMBANGAN BRT TRANS SEMARANG DENGAN PENDEKATAN SISTEM DINAMIK - Aries Susanty; Susatyo Nugroho; Kumala Ade Khantari (Diponegoro University, 2014)
[Preparation for Policy Scenarios for Developing the Bus Rapid Transit (BRT) Trans Semarang with Dynamic System Approach] Related to the complexity of the problem faced by Bus Rapid Transit (BRT) Trans Semarang, this research attempts to develop a framework for dynamic development of BRT Trans Semarang and provide a platform to support policy making related to performance improvement of BRT Trans Semarang. This research use system dynamics (SD) methodology. There are three scenarios constructed in this research and then a system dynamics model built based on them for the next five years. The first scenario is providing some feeder that will take the passenger on the bus, the second scenario is providing some new bus, and the third scenario is a combination of providing a number of feeders and also some new bus. There are three criteria which are used to evaluate the result of each scenario, i. e the achievement of the target of load factor (greater than 70%), the amount of total subsidy for operational of BRT, and percentage of the number of people that change their moda of transportation, from using private vehicles to BRT. The result of simulation with system dynamic indicated that scenario 1 is better than the existing condition; scenario 1 also better than scenario 2 or scenario 3. By providing some feeder, operational BRT can achieve the target of load factor at month 15, the government also does not need to issue subsidies for operational of BRT Trans Semarang, as well as the percentage of the number of people who moved from using private vehicles reached 26%.